2019
DOI: 10.1111/cch.12676
|View full text |Cite
|
Sign up to set email alerts
|

Does maternal attachment to her infant mediate the link between perceptions of infant crying at 6 months and parenting stress at 24 months? A structural equation modelling approach

Abstract: Background: Parenting stress is influenced by many factors including maternal attachment and excessive infant crying, yet the nature of these relationships is not well understood. For example, excessive infant crying despite maternal soothing may impact maternal attachment to the child, leading to higher stress. This paper explored whether maternal perception of excessive infant crying at 6 months was associated with higher maternal parenting stress at 24 months, and whether maternal attachment mediated this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Based on the obtained results, it can be stated that higher levels of stress among mothers of preterm-born children is related to more problematic Maternal-Infant bonding. This finding is in accordance with other findings in which a negative connection between parenting stress and Maternal-Infant bonding was observed [47,66,67]. Contrary to our expectations, in this study, there was no significant relationship between maternal postpartum bonding and either anxiety or depressive symptoms.…”
Section: Is Postpartum Bonding Associated With Maternal Mental Health (Depression Symptoms Anxiety and Stress)?supporting
confidence: 92%
“…Based on the obtained results, it can be stated that higher levels of stress among mothers of preterm-born children is related to more problematic Maternal-Infant bonding. This finding is in accordance with other findings in which a negative connection between parenting stress and Maternal-Infant bonding was observed [47,66,67]. Contrary to our expectations, in this study, there was no significant relationship between maternal postpartum bonding and either anxiety or depressive symptoms.…”
Section: Is Postpartum Bonding Associated With Maternal Mental Health (Depression Symptoms Anxiety and Stress)?supporting
confidence: 92%
“…Mothers' adult attachment styles, parenting stress and maternal-infant bonding seem to be related. Parenting stress in the first year after birth has been related both to the parent's adult attachment style [29][30][31][32] and to maternal-infant bonding [6,23]. The aim of the present study is twofold.…”
Section: Study Aimsmentioning
confidence: 97%
“…Parenting stress is often thought to arise from perceived challenges with the child's behavior, the relationship between the parent and child, and aspects related to the parent's health, life situation and perception of the parental role [22]. There is support for a negative relationship between parenting stress and maternal-infant bonding [6,23]. Parenting stress is suggested related with decreased sensitivity in parents, and increased intrusivesness and hostility towards the child [24].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal depression and anxiety have been of central interest, and maternal depressive symptoms are well established as a risk factor for poorer parenting in the early years (Lovejoy et al, 2000). For example, maternal depression has been associated with higher rates of conflict during teaching tasks (Caughy et al, 2008), as well as being shown to interfere with maternal sensitivity and motherinfant attachment (Bernard et al, 2018), and to predict increased parenting stress (Bailhache et al, 2018). Similarly, maternal anxiety has been recognized as critical for parenting (Feldman, 2007;Kendler et al, 1997), predicting lower warmth and greater hostility (Seymour et al, 2014).…”
Section: Determinants Of Parentingmentioning
confidence: 99%